INTEGRASI KOMPETENSI SISWA SD ALAM TANGERANG - Yasfi Muya Saroh; Muhammad Fauzan Muttaqin; Putri Rahayu S (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe how the integration of student competencies at Alam Tangerang Elementary School is based on the stages of child development, the programs implemented at each level, as well as to evaluate their impact on student competencies. This study adopts a descriptive qualitative approach using data collection techniques such as observation, interviews, and documentation. The study results show that the integration of student competencies at Alam Tangerang Elementary School is implemented through a tiered program across four developmental phases: The Explorer, The Survivor, The Naturalist, and The Harmonizer. Each level has a main program targeting the development of cognitive competencies, social-emotional skills, leadership, independence, and environmental awareness. Thus, effectively shaping students who are not only competent academically but also possess a strong, independent, and character-driven spirit.